2022
DOI: 10.1063/5.0107938
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing correlation between carrier mobility and defect density in MoS2 FET

Abstract: Transition metal dichalcogenides (TMDs) with only a few atoms thickness provide an excellent solution to scale down current semiconductor devices. Many studies have demonstrated that molybdenum disulfide (MoS2), a member of TMDs, is promising as a channel material to fabricate field-effect transistors (FETs). However, the carrier mobility in MoS2 FET is always far lower than the theoretical prediction. Although this poor performance can be attributed to the defects, it still lacks a quantitative analysis clari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…It should be noted that no atomic defects are observed, which are expected to be easily accessible in STM images of MoS 2 layers. 52,54,55 Therefore, we conclude that the here deposited MoS 2 nanosheets are nearly defect free due to the chosen MOVPE deposition process.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that no atomic defects are observed, which are expected to be easily accessible in STM images of MoS 2 layers. 52,54,55 Therefore, we conclude that the here deposited MoS 2 nanosheets are nearly defect free due to the chosen MOVPE deposition process.…”
Section: Resultsmentioning
confidence: 99%
“…All images are scanned in constant current mode with −1 V sample bias and 1 nA tunneling current. By the help of this method, statistical property of defect density was researched 16 .…”
Section: Methodsmentioning
confidence: 99%
“…To prevent defects from affecting the performance of TMD devices, researchers usually use optical methods 11 , 12 , probing techniques 13 16 and transmission electron techniques 17 , 18 to measure the defect distribution on each TMD surface. Optical methods have advantages, such as large area and element detection, especially excellent in X-ray photoelectron spectroscopy measurement 19 .…”
Section: Background and Summarymentioning
confidence: 99%
“…The discrepancy could arise from intrinsic defects in TMD materials. Several studies have indicated that defects are largely responsible for the poor performance of TMD-derived devices. For instance, a recent work has demonstrated the mobility of MoS 2 FET is correlated to the concentration of surface defects . Nevertheless, good control over the defects during sample preparation by either exfoliation or growth methods is nearly impossibleintrinsic defects are usually inevitable. Many studies have attempted to control the numbers or types of defects after TMD samples are synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…13−17 For instance, a recent work has demonstrated the mobility of MoS 2 FET is correlated to the concentration of surface defects. 17 Nevertheless, good control over the defects during sample preparation by either exfoliation or growth methods is nearly impossible� intrinsic defects are usually inevitable. 18−24 Many studies have attempted to control the numbers or types of defects after TMD samples are synthesized.…”
Section: Introductionmentioning
confidence: 99%